Validation of a human-serum-based in vitro growth method for drug screening on juvenile development stages of Schistosoma mansoni. - Valentin Buchter; Pierre H H Schneeberger; Jennifer Keiser (Public Library of Science (PLoS), 2021)
Background Schistosomiasis affects over 200 million people worldwide but only praziquantel is available for treatment and control. Drug discovery is often based on phenotypic drug screening, involving different parasite stages retrieved from infected mice. Aiming to reduce animal use, we validated an in vitro growth method for juvenile Schistosoma mansoni for the purpose of drug sensitivity assays. Methodology/principal findings We compared inter-batch variability of serum, worm size and organ development, gender distribution, and drug sensitivity between in vitro and in vivo grown worms over different life stages. In vitro developed S. mansoni in Hybridoma medium supplemented with 20% human serum were similar in size as in vivo worms until 28 days of incubation (males 1.4 ± 0.2 mm, females 1.1 ± 0.5 mm long). qPCR analysis revealed similar gender distribution both on newly transformed schistosomula and worms grown for 21 days. Worms developed in vitro and in vivo were similarly sensitive to praziquantel from 7 to 35 days of development with the exception of 21 days of development, where a slightly lower activity was observed for the in vitro grown worms (IC50: 0.54 μM in vitro, 0.14 μM in vivo 72 hours post-incubation). The evaluation of five additional drugs revealed a similar sensitivity on worms developed for 21 days, with the exception of mefloquine, where we observed a 10-fold lower sensitivity on in vitro developed schistosomes when compared to in vivo grown (IC50: 4.43 μM in vitro, 0.48 μM in vivo). Conclusion A large number of juvenile S. mansoni worms can be grown in vitro, which show similar drug sensitivity, gender distribution, size and morphology as the worms recovered from rodents, supporting the use of this method in drug screening efforts.